Implications of fintech revolution in the efficiency of regional innovation: Insights from Jordan - Ali, Mohammad Sami; Alataibi, Mahmud; Alabdullatif, Sultan; Baqader, Saleh; Hariri, Mohammad (International Journal of Innovative Research and Scientific Studies, 2025)
Due to digital transformation in finance, researchers have paid dramatic attention to evaluating the impact of financial technology on regional innovation efficiency. Hence, since Fintech’s ability is found to significantly influence local innovation, the current research was primarily designed to scrutinize the relationship between financial technology (Fintech) and regional innovation efficiency in Jordan. Moreover, by utilizing the dynamic spatial Durbin model, the study provided empirical evidence for the impact of Fintech’s spatial spillover in a sample of 12 Jordanian Governorates for the period 2013-2022. Consequently, the findings proved that there is a noteworthy worldwide spatial correlation and time dependence of regional innovation efficiency during the study period. Additionally, Fintech improves regional innovation efficiency, and this effect has a large positive spatial spillover. Therefore, the study recommends that the financial sector in Jordan use innovative strategies and financial technology to boost regional innovation efficiency and technological innovation.